Students from Manzanillo in the prevention of COVID-19 - Gabriela Amarilis García Proenza; Daliana de la Caridad Prieto Tabernilla; Claudia Ivett Rodríguez Santiesteban; Aracelis Montoya Vázquez; Jany González De Sosa; Maylin Pérez Gutiérrez (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: Students constitute a bulwark in the work of active COVID-19 screening, developing actions for the prevention of the disease. Aim: to characterize the actions carried out by students during COVID-19 screening at the René Vallejo Ortiz Health Center in the municipality of Manzanillo, from March 18 to May 31, 2020. Method: an Observational-Descriptive-Cross-sectional study was carried out. The universe consisted of 229 students, for which a non-probabilistic sampling was used, in addition to complying with the inclusion criteria stated for the study. Variables studied were: career, academic year, evaluation of research activities, and preventive actions. Data was processed according to descriptive statistics. Results: it was found a predominance of students of Medicine (93.4%), the fifth year reported the highest percentage (26.6%). The majority of evaluations were excellent in the activities carried out (79 %), the whole population was screened without cases of COVID-19 and prevention actions for the disease were provided. Conclusions: the participation of students in the screening allowed access to all patients, screening them daily to determine respiratory diseases and carry out COVID-19 preventive actions.